Water-induced blue-green variable nonconventional ultralong room temperature phosphorescence from cross-linked copolymers via click chemistry - Gao, Liang (2022)
Ultralong room temperature phosphorescence is employed in information encryption, chemical sensing, lighting, and imaging on account of its long lifetime and high signal-to-noise ratio. As the triplet excitons can be easily quenched and interfered by nonradiative transition process, it is difficult to obtain long-lived phosphorescence through conventional methods. Herein, a general design strategy to form cross-linked networks by click chemistry is presented for efficiently promoting the phosphorescence performance. Using the hydrogen bonding interactions formed between C-O···H-N units and covalently cross-linked network by the B-O bond, the rigidity of the entire system is greatly enhanced, so the radiative transition process is well strengthened. Interestingly, under the influence of water molecule, the afterglow colors of the system change from blue (488 nm) to green (510 nm). Because of the presence of cross-linked network, the emission is not directly quenched when the system is intervened by water. Having long phosphorescence lifetime (841.06 ms) and high quantum yield (10.48%), the obtained system is utilized for anti-counterfeiting demonstration. This strategy paves a new way for the design of amorphous ultralong room temperature phosphorescence materials by efficient and user-friendly click chemistry.